The amount of preoperative endometrial tissue surface in relation to final endometrial cancer classification - Vrede, S W; Hulsman, A M C; Reijnen, C; Van de Vijver, K; Colas, E; Mancebo, G; Moiola, C P; Gil-Moreno, A; Huvila, J; Koskas, M; Weinberger, V; Minar, L; et al. (Gynecologic oncology, 2022)
OBJECTIVE: To evaluate whether the amount of preoperative endometrial tissue surface is related to the degree of concordance with final low- and high-grade endometrial cancer (EC). In addition, to determine whether discordance is influenced by sampling method and impacts outcome. METHODS: A retrospective cohort study within the European Network for Individualized Treatment of Endometrial Cancer (ENITEC). Surface of preoperative endometrial tissue samples was digitally calculated using ImageJ. Tumor samples were classified into low-grade (grade 1-2 endometrioid EC (EEC)) and high-grade (grade 3 EEC + non-endometroid EC). RESULTS: The study cohort included 573 tumor samples. Overall concordance between pre- and postoperative diagnosis was 60.0%, and 88.8% when classified into low- and high-grade EC. Upgrading (preoperative low-grade, postoperative high-grade EC) was found in 7.8% and downgrading (preoperative high-grade, postoperative low-grade EC) in 26.7%. The median endometrial tissue surface was significantly lower in concordant diagnoses when compared to discordant diagnoses, respectively 18.7 mm2 and 23.5 mm2 (P = 0.022). Sampling method did not influence the concordance in tumor classification. Patients with preoperative high-grade and postoperative low-grade showed significant lower DSS compared to patients with concordant low-grade EC (P = 0.039). CONCLUSION: The amount of preoperative endometrial tissue surface was inversely related to the degree of concordance with final tumor low- and high-grade. Obtaining higher amount of preoperative endometrial tissue surface does not increase the concordance between pre- and postoperative low- and high-grade diagnosis in EC. Awareness of clinically relevant down- and upgrading is crucial to reduce subsequent over- or undertreatment with impact on outcome.
Keywords: endometrium; biopsie; Female; Carcinoma, Endometrioid; nádory endometria; retrospektivní studie; Biopsy; Endometrial Neoplasms; endometroidní karcinom; ženské pohlaví; Humans; lidé; Retrospective Studies; Endometrium